PERANCANGAN APLIKASI PRESENSI KODE QR SEBAGAI PENDUKUNG SISTEM PENGGAJIAN UNTUK MANAJEMEN UMKM - Edryan, Darwin; Tendean, Sandi; Darmianto , Amok (LPPM Universitas Widya Dharma Pontianak, 2024)
Small Medium Enterprise (SME) frequently still use manual recording to manage staff attendance and payroll, which leads to errors and inefficiencies. The goal of this research is to create a mobile web payroll system that is integrated with an Android application based on QR codes to enhance the accuracy and efficiency of payroll processing for employees of small and medium-sized businesses. The attendance application was developed in Android Studio with the Java programming language, while the payroll system was developed with HTML, CSS, and JavaScript. A cloud-based database platform called Firebase is utilized. This research uses the Unified Modeling Language (UML) modeling method. The attendance application is able to record employee attendance automatically through QR code scanning. The payroll system provides full control for SME owners, allowing the process of controlling, monitoring, and printing accurate attendance and payroll reports. The use of this attendance application and payroll system will reduce manual errors, improve operational efficiency, and provide real-time control to SME owners. The integration of the attendance application and employee payroll system is very important to improve the competitiveness and adaptability of SMEs in the digital era. Keywords— SME, QR code, Attendance recording, Employee payroll